Connecting Australian First Nations’ Histories with Settler Colonial Winegrape Cultivation - McIntyre, Julie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2023)
The global diffusion of winegrapes (Vitis vinifera) from western Europe to European colonies since the fifteenth century is often historicized as a benefit bestowed upon those colonial places rather than an invasion of ecologies where sovereign Indigenous peoples knowingly managed their land. British colonists in Australia associated wine production and consumption symbolically with imperial and colonial power, envisaging the material advantage of domestic and export profits and social appeasement within the emergent colonial order. Settler colonial winegrowing is thus a salient site for observing settler-Indigenous relations. This article expands upon my earlier collaborations with non-Indigenous scholars on the topic of settler-Indigenous relations in winegrowing and consumption to highlight First Nations’ experiences of colonization.